CdS-based artificial leaf for photocatalytic hydrogen evolution and simultaneous degradation of biological wastewater. (August 2022) - Fan, Yingying; Yang, Ruijie; Zhu, Rongshu; Zhao, Heng; Lu, Qingye; Chen, Zhangxing; Hu, Jinguang
Abstract: Rational design of all-solid-state Z-scheme heterojunction with advanced structure is essential for boosting photocatalytic efficiency. Herein, we design and fabricate a novel Z-scheme photocatalyst with leaf architecture (named artificial leaf) via a simple dipping-calcination (DC) process followed by a successive ionic layer adsorption and reaction (SILAR) strategy. The prepared artificial leaf, composing of CdS, InVO4, and BiVO4, holds advanced leaf-like structure and Z-scheme electron transfer pathway. As a result, this novel artificial leaf exhibits outstanding capability for the harvesting of visible light and superior efficiency for the separation of photogenerated electron-hole pairs, as well as remarkably enhanced photocatalytic performance and stability for H2 evolution (with the rate of 5033 μm g −1 ∙h −1 ) and pollution degradation (46% pollution can be degraded within 3 h). Graphical abstract: Image 1 Highlights: Artificial leaf CdS–BiVO4 –InVO4 Z-scheme heterojunction system was synthesized. Artificial leaf CdS–BiVO4 –InVO4 holds advanced leaf-like structure and Z-scheme electron transfer pathway. Artificial leaf CdS–BiVO4 –InVO4 shows outstanding capability for visible light harvesting and carrier separation. Artificial leaf CdS–BiVO4 –InVO4 exhibits an excellent photocatalytic activity for H2 production and degradation of pollutants.